2021
DOI: 10.1186/s12954-021-00488-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional status among patients undergoing maintenance treatments for opioid use disorders

Abstract: Background Methadone and buprenorphine are the most prevalent types of opioid maintenance programs in Andalusia. The main objective is comparing the functional status of patients with pharmacological opioid maintenance treatments according to different socio-demographic characteristic, health and disabilities domains and sexual difficulties. Methods A total of 593 patients from the Andalusia community, 329 were undergoing methadone treatment and 26… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Studies comparing methadone and buprenorphine with regard to the occurrence of SDs in male and female patients have to date shown mixed results. Ruíz Ruíz et al found the prevalence of SDs to be higher in the methadone group ( 36 ), whereas other studies did not find beneficial effects of buprenorphine ( 56 ). Therefore, the recommendation of switching from methadone to buprenorphine in MMT patients with SDs is not unequivocally supported by literature.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies comparing methadone and buprenorphine with regard to the occurrence of SDs in male and female patients have to date shown mixed results. Ruíz Ruíz et al found the prevalence of SDs to be higher in the methadone group ( 36 ), whereas other studies did not find beneficial effects of buprenorphine ( 56 ). Therefore, the recommendation of switching from methadone to buprenorphine in MMT patients with SDs is not unequivocally supported by literature.…”
Section: Discussionmentioning
confidence: 98%
“…It also raises the question whether substance-use related lifestyle factors or opioid agonists themselves play a large role in the emergence of SDs in this patient population. Regarding the latter, studies have repeatedly demonstrated that male patients in MMT suffer from SDs more often when compared to patients receiving treatment with buprenorphine ( 35 , 36 ). This suggests that methadone itself contributes partly to the occurrence of SDs in opioid-dependent men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation